Aboveground biomass of Tectona grandis plantations in Costa Rica - Pérez Cordero, L.D.; Kanninen, M. (2003)
There are few studies on biomass distribution for Tectona grandis plantations in Costa Rica. This paper reports the distribution of total aboveground biomass of T. grandis and its relationship with diameter at breast height (dbh), age and stand density in plantations across Costa Rica. Foliage, branch, stem and total aboveground biomass were highly correlated both with dbh (r > 0.91) and with age (r < 0.85). Foliage dry biomass represented between 1 and 6% of the total tree dry biomass, while 5 to 30% corresponded to branches and 70 to 90% to stem dry weight. Per hectare aboveground biomass tended to incease with increasing age class (young, intermediate and mature). Foliage dry biomass varied between 3 and 9 Mg Ha-1, branch dry biomass between 11 abd 54 Mg Ha-1, stem dry biomass between 70 and 221 Mg ha-1, and total aboveground dry biomass between 84 and 284 Mg ha-1, and total aboveground dry biomass between 84 and 284 Mg ha-1. Significant relations between crown diameter and aboveground biomass with dbh, age and stand density, useful for the management of stand competition, are the main results of this study.